2016
DOI: 10.1002/cpt.329
|View full text |Cite
|
Sign up to set email alerts
|

Transparency and Reproducibility of Observational Cohort Studies Using Large Healthcare Databases.

Abstract: The scientific community and decision-makers are increasingly concerned about transparency and reproducibility of epidemiologic studies using longitudinal healthcare databases. We explored the extent to which published pharmacoepidemiologic studies using commercially available databases could be reproduced by other investigators. We identified a nonsystematic sample of 38 descriptive or comparative safety/effectiveness cohort studies. Seven studies were excluded from reproduction, five because of violation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
154
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 33 publications
2
154
0
1
Order By: Relevance
“…PSs were estimated using logistic regression models that included the following baseline patient characteristics: age on index, gender, urinary tract infections (UTIs), diseases of the genitourinary system, hospitalization for bacterial infections, prior use of immune‐modulating or ‐suppressing drugs, HIV/AIDS, cancer, obesity, cardiovascular disease (CVD), microvascular disease, alcohol abuse, liver and renal disease, and chronic obstructive pulmonary disease (COPD). Analysis was performed using the Aetion Evidence Platform version 3.13 …”
Section: Methodsmentioning
confidence: 99%
“…PSs were estimated using logistic regression models that included the following baseline patient characteristics: age on index, gender, urinary tract infections (UTIs), diseases of the genitourinary system, hospitalization for bacterial infections, prior use of immune‐modulating or ‐suppressing drugs, HIV/AIDS, cancer, obesity, cardiovascular disease (CVD), microvascular disease, alcohol abuse, liver and renal disease, and chronic obstructive pulmonary disease (COPD). Analysis was performed using the Aetion Evidence Platform version 3.13 …”
Section: Methodsmentioning
confidence: 99%
“…All studies of interest were selected from a non‐systematic sample of peer‐reviewed database studies, published between 2008 and 2014. Wang et al assessed the reproducibility of these studies in Aetion using the same Optum/United data source and study design to match the reported results …”
Section: Methodsmentioning
confidence: 99%
“…Each study with the exception of angioedema events in association with use of drugs that act on the renin–angiotensin–aldosterone system included the basic confounders with deciles of the propensity score and deciles of the trimmed propensity score in their assessment (Table ). Basing our comparison across approaches on the results presented in Wang et al , we did not have any basis of comparison for these two assessments . We looked for marked differences in the treatment effect estimates across the fixed and expanded look‐back approaches, as well as meaningful increases in the prevalences of covariates captured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As others have noted, reporting the specific codes used to define these measures is critical for transparency and reproducibility 47,63 especially in databases where there can be substantial ambiguity in code choice.…”
Section: Exposure Outcome Follow Up Covariates and Various Cohormentioning
confidence: 99%